2009
DOI: 10.1254/jphs.09012fp
|View full text |Cite
|
Sign up to set email alerts
|

Oxymetazoline Inhibits and Resolves Inflammatory Reactions in Human Neutrophils

Abstract: Abstract. The nasal decongestant oxymetazoline (OMZ) exhibits anti-oxidative and antiinflammatory properties (I. Beck-Speier et al., J Pharmacol Exp Ther. 2006;316:842-851). In a follow up study, we hypothesized that OMZ generates pro-resolving lipoxins being paralleled by production of immune-modulating prostaglandin E 2 (PGE 2 ) and anti-inflammatory 15(S)-hydroxy-eicosatetraenoic acid [15(S)-HETE] and depletion of pro-inflammatory leukotriene B 4 (LTB 4 ). Human neutrophils (PMN) were chosen as the cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
14
0
1
Order By: Relevance
“…This was due to the oxidative potential of the particles; we found that particles were able to oxidise the amino acid methionine to methionine sulfoxide, and that they showed an ESR signal equivalent to a free radical within the particle core [23]. The pro-resolving mediator LXA 4 also increased during particle incubation, which is in agreement with our recent findings with human neutrophils [35]. LXA 4 is generated via PGE 2 and 15(S)-HETE and represents a stop signal for inflammation to return the inflamed tissue to homeostasis [36].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This was due to the oxidative potential of the particles; we found that particles were able to oxidise the amino acid methionine to methionine sulfoxide, and that they showed an ESR signal equivalent to a free radical within the particle core [23]. The pro-resolving mediator LXA 4 also increased during particle incubation, which is in agreement with our recent findings with human neutrophils [35]. LXA 4 is generated via PGE 2 and 15(S)-HETE and represents a stop signal for inflammation to return the inflamed tissue to homeostasis [36].…”
Section: Discussionsupporting
confidence: 86%
“…Due to the oxidative potential of UFCP [23], arachidonic acid is non-enzymatically oxidized to 8-isoprostane, used as a marker for redox imbalance. Arachidonic acid serves as a substrate for the downstream pathways of COX (cyclooygenase), 15- and 5-LO (15- and 5-lipoxygenase), leading to formation of prostaglandins such as PGE 2 , 15(S)-HETE, leukotrienes such as LTB 4 and to LXA 4 via PGE 2 activated 15-LO [23,26,35]. Because these processes are predominantly located in the nuclear membrane or perinuclear space, these products of these pathways may influence gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being an a-agonist, oxymetazoline has been shown to have various antioxidative and anti-inflammatory properties. [8][9][10][11][12] Whether any of these effects contributed to our results is unknown. The oxymetazoline was dosed once daily at night.…”
Section: Discussionmentioning
confidence: 93%
“…В осно-ве указанного эффекта лежит ингибирование экспрес-сии молекул ICAM-1, обеспечивающих адгезию вирус-ных частиц к клеткам респираторного эпителия [19]. Результаты последующих лабораторных исследований показали, что оксиметазолин обладает также антиокси-дантными и противовоспалительными свойствами [20].…”
Section: сосудосуживающие препараты (деконгестанты)unclassified